2020
DOI: 10.1136/sextrans-2019-054345
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and sexual health service use of MSM engaging in chemsex: results from a large online survey in England

Abstract: BackgroundChemsex, the use of select psychoactive drugs to enhance sexual experience, typically among men who have sex with men (MSM), is associated with sexual behaviours with higher STI risk. Understanding patterns of chemsex among MSM as well as the characteristics and sexual health service engagement of chemsex participants is important for developing interventions.MethodsBetween 5/2016 to 5/2017, 3933 MSM completed an online survey, recruited in sexual health clinics (SHCs) in England (n=421) and via four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 12 publications
6
29
2
7
Order By: Relevance
“…Unlike other studies, we asked specifically about the use of individual chemsex drugs and found a very common use of poppers, cocaine, methamphetamine and GHB/ GBL. These results differ slightly from those observed in other countries and other Spanish regions, where mephedrone was one of the main sexualized drugs among MSM [29,30], and demonstrate the dynamic nature and cultural variation of chemsex phenomenon, a fact that has to be taken into account when designing specific prevention strategies [31]. The social and personal factors involved in chemsex are as diverse as the barriers to reduce HCV-related sexual risk behaviour in this population, including social pressure, and HCV-HIV and drug consumption stigma [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike other studies, we asked specifically about the use of individual chemsex drugs and found a very common use of poppers, cocaine, methamphetamine and GHB/ GBL. These results differ slightly from those observed in other countries and other Spanish regions, where mephedrone was one of the main sexualized drugs among MSM [29,30], and demonstrate the dynamic nature and cultural variation of chemsex phenomenon, a fact that has to be taken into account when designing specific prevention strategies [31]. The social and personal factors involved in chemsex are as diverse as the barriers to reduce HCV-related sexual risk behaviour in this population, including social pressure, and HCV-HIV and drug consumption stigma [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Women-identifying participants also reported a higher odds of oral sex, consistent with a quantitative study in Thailand that suggested TGW were more likely than MSM to prefer receptive anal sex and engage in only oral sex [44]. Moreover, our study identified an association between mobile phone ownership and oral sex, a sexual practice that has not been differentiated from anal sexual practices in prior studies [45][46][47].…”
Section: Plos Onesupporting
confidence: 85%
“…There are a number of concerns around chemsex, though most notable are concerns about high rates of addiction, increased HIV transmission rates, and sexual assault which occurs when people are under the influence of these drugs (see Blomquist et al, 2020;Bourne et al, 2014;Bourne et al, 2015;Public Health England, 2015;Stevens et al, 2020). After an official review in Novemeber 2020, GHB and GBL werereclassified as class B drugs in March 2021.…”
Section: Introductionmentioning
confidence: 99%